Clays and Clay Minerals, Vol. 59, No. 1, 75–94, 2011. - Karakaya, Muazzez Celik; Karakaya, Necati; Kupeli, Suayip (My University, 2011)
A number of different types of bentonite deposits formed by hydrothermal alteration and diagenetic processes are to be found in the Ordu area of the Eastern Black Sea region. The Ca- and Na-bentonite deposits are related to Upper Cretaceous tholeitic to calc-alkaline volcanites, predominantly dacite and andesite, and also include rhyodacite with lesser basalt and their pyroclastic equivalents. In the present study, dacite (PR1), perlite (PR2), moderately altered rocks (MPR), and Na- and Ca-bentonites were studied to describe and compare their mineralogical and geochemical properties and their conditions of formation by means of X-ray diffraction, optical microscopy, scanning electron microscopy, and chemical analytical techniques. Ca-bentonites, except for smectite, contain opal-CT, feldspar, biotite, and rarely pyrite, while Na-bentonites contain smectite and less feldspar, opal-CT, kaolinite, and illite. Progressive alteration of the PR2 caused depletion in K2O andNa2O and enrichment in MgO and CaO in all of the Ca-bentonite samples. Na2O was depleted in all of the Na-bentonites and in most of theMPR. The medium and heavy rare earth elements (MREE and HREE) show mass gain or mass loss in the Na-bentonites. The HREE show nearly immobile behavior in the Ca-bentonites. The rare earth elements (REE) and transition elements (TRE) mostly gained mass in the Ca-bentonites in contrast to Na-bentonites. Large-ion lithophile elements (LILE) are strongly depleted in all of the bentonites. The LREE, MREE, and HREE were strongly depleted in most of the MPR samples. TiO2, Lu, Tm, and Tb show immobile behavior in all samples. PR1 exhibits a slightly positive Eu anomaly. Two MPR samples show slightly positive Eu anomalies (1.03, 1.13), and one Na-bentonite sample displays a slightly positive Eu anomaly (1.04). Most of the Nabentonites have weakly negative Eu anomalies, whereas perlite and the Ca-bentonite have a strongly negative Eu anomaly. The PR1, PR2, MPR, and Na-bentonite present a positive Ce anomaly, and the Ca-bentonite shows a moderately negative Ce anomaly. The Ca-montmorillonites are mainly hydrothermal in origin and derived from alteration of volcanoclastic material in situ and/or in the subaerial environment. The Na-montmorillonites formed by alteration and diagenesis of volcanoclastic material in the sedimentary basin
Mineralogical And Geochemical Properties Of The Na- And Ca-bentonites Of Ordu (ne Turkey)
gsccm59109-kar.pdf-- 1.66MB
Keywords: Periodicals; Geology; Bentonite; Genesis; Geochemistry; Hydrothermal Alteration; Mass Balance; Ordu; Smectite; Trace Elements; Turkey